Supporting Factors and Obstacles to Local Government Organizational Communication in Building Islamic Sharia Pilot Villages through Islamic Education in Bireuen District - Jufliwan Jufliwan; Abdullah Abdullah; Rubino Rubino (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Due to a variety of causes, the Bireuen district has failed to significantly improve the lives of village communities in all of their activities to attain prosperity, harmony, and peace in line with Islamic law. 62 communities helped create Islamic sharia pilot villages in Bireuen Regency from 2006 to 2021. Village officials, women, and youth will be trained in 5 communities in 2021. The targeted activity hasn't accommodated the sharia economy's physical development and empowerment.This research focuses on the supporting and inhibiting elements of local government organizations in creating Islamic sharia pilot villages in Bireuen district to make it more direct, easy to comprehend, efficient, and successful and to serve as a reference.This study employed qualitative descriptive analysis. Bireuen, Aceh Province, hosted this study. From February to July 2022, research is conducted in stages.This study selected informants purposefully (deliberately). The purposive method selects study subjects based on particular criteria. This study interviewed the Keuchik, Imum Meunsah, Peutuha Tuha Peut, and young leaders of the Islamic law pilot villages/gampongs in Bireuen district.Local Government Media Building Islamic Sharia Pilot Villages in Bireuen District Strengthening oral communication media through loudspeakers, written media like announcements, wall magazines, brochures, and technology channels like whatsapp groups for village community empowerment increases knowledge, attitudes, skills, behavior, abilities, awareness, and resource use through policies, programs, activities, and assistance in accordance with the Distortion of Communication Messages from Local Government. Lack of human resources, budgeting, and the Bireuen District qanun or Bireuen Regent Regulations limit local government organizations' communication in building Islamic Sharia pilot villages in Bireuen Regency.